PENGARUH LINGKUNGAN SEKOLAH TERHADAP RESILIENSI SISWA DALAM MENGATASI TOXIC FRIENDSHIP DI SMA SWASTA NASRANI 2 MEDAN - Gladis Rebeka Sinaga; Sanggam Pardede; Elisabeth Margareta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the school environment on students' resilience in dealing with toxic friendship, with toxic friendship acting as a mediating variable at SMA Swasta Nasrani 2 Medan. This research employed an explanatory quantitative approach using a total sampling technique involving 70 students as respondents. Data were collected through a Likert-scale questionnaire and analyzed using linear regression, partial test, and Sobel test with the assistance of SPSS Version 26. The results indicate that the school environment has a positive and significant effect on students' resilience, with a t-value of 6.303 and a significance level of 0.000. In addition, the school environment also has a positive and significant effect on toxic friendship, with a t-value of 19.868 and a significance level of less than 0.001. Furthermore, toxic friendship shows a positive and significant effect on students' resilience, with a t-value of 4.434 and a significance level of less than 0.001. Moreover, the mediation test reveals that toxic friendship significantly mediates the relationship between the school environment and students' resilience, as indicated by a t-value of 3.202 and a significance level of 0.001. These findings suggest that a conducive school environment contributes to enhancing students' resilience, both directly and indirectly through the formation of healthier peer relationships. Therefore, it is essential for schools to create a supportive environment in order to strengthen students' mental resilience.